Bank Ownership and Decline in Loan Growth due to the Pandemic - Bitia, Ruthana; Dalimunthe, Zuliani (The Indonesian Capital Market Review, 2022)
This study aims to analyze the effect of bank ownership structure on loan growth before and during the pandemic. Specifically, we developed four models to capture different loan types provided in the Indonesian banking system; working capital, investment, consumer, and total loan growth. This study used 150 observations of commercial banks for 2019 (before the pandemic) and 2020 (during the pandemic). We conducted the regression method to test hypotheses. The main finding of this study was that foreign banks’ consumer credit growth significantly lower than domestic banks. Similar findings occurred for other types of loans, and this conclusion has controlled for the adverse effects of the pandemic. This finding means that foreign banks in Indonesia are not substitutes for loan suppliers in the domestic market and tend to behave pro-cyclical. The government needs to carry out regulations to reduce the risk-accelerate nature of foreign banks in the Indonesian economy